2001
DOI: 10.1210/jcem.86.8.7749
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow and Glucose Metabolism in Hypothyroidism: A Positron Emission Tomography Study

Abstract: Hypothyroidism is often associated with defective memory, psychomotor slowing, and depression. However, the relationship between thyroid status and cognitive or psychiatric disturbances remains unclear. Using psychometric scales, 10 patients who had undergone total thyroidectomy for thyroid carcinoma were evaluated for depression, anxiety, and psychomotor slowing; they were examined both when euthyroid and hypothyroid after thyroid hormone withdrawal. Positron emission tomography was used, with oxygen-15-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(44 citation statements)
references
References 26 publications
5
39
0
Order By: Relevance
“…Regional CBF alterations have been detected in the bilateral parietal lobes and in the bilateral occipital lobes, which extended to the prefrontal cortices as hypothyroidism worsened. However, these results were partly disputed in a study that correlated regional CBF and glucose metabolic activity, evaluated with the positron emission tomography 18F-labeled 2-deoxy-2-fluoro-D-glucose method, with the mental state of ten patients affected by severe hypothyroidism (TSH: 109.83G40.25 mU/l) (39). That study identified a global but not regional reduction of CBF and glucose metabolic activity which may reflect a direct effect of thyroid failure on the overall brain activity.…”
Section: Effects On Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional CBF alterations have been detected in the bilateral parietal lobes and in the bilateral occipital lobes, which extended to the prefrontal cortices as hypothyroidism worsened. However, these results were partly disputed in a study that correlated regional CBF and glucose metabolic activity, evaluated with the positron emission tomography 18F-labeled 2-deoxy-2-fluoro-D-glucose method, with the mental state of ten patients affected by severe hypothyroidism (TSH: 109.83G40.25 mU/l) (39). That study identified a global but not regional reduction of CBF and glucose metabolic activity which may reflect a direct effect of thyroid failure on the overall brain activity.…”
Section: Effects On Lipidsmentioning
confidence: 99%
“…The reduction is unlikely to have been due to increased vascular resistance alone, since glucose metabolism was also impaired. This condition might be clinically reflected in the observed slowing of psychomotor function in patients rather than in their states of clinical depression (39). This mental state was interpreted as resulting from the abruptly induced deficiency of thyroid hormone, which led to the incapacity of brain cells to extract an adequate amount of oxygen and glucose from the blood.…”
Section: Effects On Lipidsmentioning
confidence: 99%
“…It was not until decades later, however, that the use of nuclear magnetic resonance (NMR) spectroscopy, contemporary nuclear medicine technology (e.g., positron emission tomography (PET)), and improved statistical methodologies allowed for a reinterpretation of some of the findings from work performed much earlier. Strong support soon grew for a correlation between thyroid function and cerebral neuronal activity (Constant et al, 2001;Marangell et al, 1997;Smith and Ain, 1995), clearly not explainable by changes in vascular resistance alone (Constant et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Using PET to explore cerebral blood flow (with oxygen-15 water) and metabolism (with fluorine-18 fluorodeoxyglucose) in severe, transient hypothyroidism, Constant's group (Constant et al, 2001) demonstrated global decreases in both functional parameters but no significant regional changes. Using single photon emission computed tomogram (SPECT), the other standard nuclear medicine technique to investigate the brain, two groups have published studies exploring the distribution of a lipophilic, single photon emitting cerebral radiotracer-a so-called regional cerebral blood flow (rCBF) agent-in patients with hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, depression may be accompanied by various subtle thyroid abnormalities. Relatively few previous functional neuroimaging studies have investigated the neural correlates of mood dysfunction in patients with hypothyroidism (Bauer et al 2009;Constant et al 2001;Nagamachi et al 2004;Schraml et al 2006;Zhu et al 2006), and these studies reported cerebral hypoperfusion as the most consistent finding (Bauer et al 2009;Constant et al 2001;Forchetti et al 1997;Kinuya et al 1999;Krausz et al 2007;Krausz et al 2004;Nagamachi et al 2004;Schraml et al 2006). In a subgroup of patients, this hypoperfusion subsided after thyroid replacement therapy (Bauer et al 2009).…”
Section: Introductionmentioning
confidence: 95%